Evaluation of licorice flavonoids as protein tyrosine phosphatase 1B inhibitors - Li, Wei; Li, Songpei; Higai, Koji; Sasaki, Tatsunori; Asada, Yoshihisa; Ohshima, Shigeru; Koike, Kazuo (Bioorganic & medicinal chemistry letters, 2013)
Protein tyrosine phosphatase 1B (PTP1B) is a major negative regulator in insulin- and leptin-signaling cascades as well as a positive regulator in tumorigenesis, and much attention has been paid to PTP1B inhibitors as potential therapies for diabetes, obesity, and cancer. In the present study, the screening of a compound library of licorice flavonoids allowed for the discovery of several compounds, including licoagrone (3), licoagrodin (4), licoagroaurone (5), and isobavachalcone (6), as new PTP1B inhibitors. It was revealed that these compounds inhibit the activity of PTP1B in different modes and with different selectivities and that they exhibit different cellular activity in the insulin-signaling pathway. Glycybenzofuran (1), a competitive PTP1B inhibitor, showed both excellent inhibitory selectivity against PTP1B and cellular activity on the insulin-stimulated Akt phosphorylation level. The similarity of its action profiling in the insulin-signaling pathway suggested its potential as a new anti-insulin-resistant drug candidate.